Friendly visiting and partial enquiry (proof copy)
1902-02 1902 1900s 15 pages 7 The number of patients found able to repay the cost of their surgical appliances increases, and the cases are few in which some part of the cost is not repaid. Against the depressing returns of patients known to have joined Provident Dispensaries and Friendly Societies (five and seven respectively), the Almoner would lay stress on the fact that cases not infrequently come under her notice where the efforts made by Miss Stewart four or five years ago are only now bearing fruit, as well as on the fact that many patients are kept for months in view before they are eligible for any club. In response to the request and in recognition of the difficulties of the Almoners who are in the out patient department of hospitals endeavouring to work on the lines of general charity, the Charity Organisation Society has recommended that its District Committees undertake to pay friendly visits to patients on behalf of the Almoners, or to verify, if needs be, statements made to Almoners, without, as heretofore, requiring the patient to apply in person at the office of the Committee. This is in the first instance to be experimental, and with the understanding that the patient be informed that his statement will be so verified. It is hoped that such a system of friendly visiting will enable the Almoner to report to the medical officer on the condition of the patient's surroundings and to ensure a better chance of his wishes being carried out. It is gratifying to the Almoner to feel that the kindness and courtesy of the medical staff enable her to be of considerable use to the neighbouring C.O.S. Committees in obtaining for them special and careful opinions upon cases of difficulty with which they may be dealing. May 11, 1901. (2) THREE MONTHS' WORK, FROM APRIL 1 TO JUNE 30, 1901. Number of patients interviewed, 1,545, being 515 per month. Ten patients were referred to Poor Law. Thirty-five patients sent away as able to pay for treatment. One patient retained at request of surgeon on giving donation to hospital. Of those sent away, several were patients treated at gate, who only by chance came under the notice of the Almoner. This and the increasing number of gate casualties suggests the fear that patients other than accidents and emergency cases are treated at the gate. 378/IMSW/A/1/1/9